2023
DOI: 10.3390/antiox12020355
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Human DNA Glycosylase NEIL2 Is Affected by Oxidative Stress and Modulates Its Activity

Abstract: The DNA glycosylase NEIL2 plays a central role in maintaining genome integrity, in particular during oxidative stress, by recognizing oxidized base lesions and initiating repair of these via the base excision repair (BER) pathway. Post-translational modifications are important molecular switches that regulate and coordinate the BER pathway, and thereby enable a rapid and fine-tuned response to DNA damage. Here, we report for the first time that human NEIL2 is regulated by phosphorylation. We demonstrate that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Holst et al [ 6 ] have demonstrated for the first time that NEIL2 is phosphorylated by the two kinases in vitro and in human neuroblastoma cells: cyclin-dependent kinase 5 (CDK5) and protein kinase C (PKC). Post-translational modifications such as phosphorylation are generally known to serve as molecular switches providing a fast and fine-tuned response to acute oxidative stress.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Holst et al [ 6 ] have demonstrated for the first time that NEIL2 is phosphorylated by the two kinases in vitro and in human neuroblastoma cells: cyclin-dependent kinase 5 (CDK5) and protein kinase C (PKC). Post-translational modifications such as phosphorylation are generally known to serve as molecular switches providing a fast and fine-tuned response to acute oxidative stress.…”
mentioning
confidence: 99%
“…Importantly, the authors demonstrated that this phosphorylation is rapidly reversed in response to oxidative stress rendered by treatment with hydrogen peroxide in human neuroblastoma cells. In paper [ 6 ], a working model of the phosphorylation state of NEIL2 is discussed. At a basal level, NEIL2 is phosphorylated by CDK5/PKC.…”
mentioning
confidence: 99%
See 1 more Smart Citation